2013
DOI: 10.1016/j.jemermed.2012.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Observation Units for Young Emergency Department Chest Pain Patients

Abstract: 2Background: Determining which patients presenting to the emergency department (ED) require

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…recent studies have had variable results with positive stress test rates ranging from 3% to 6%. 11,12 However, all the positive stress tests in these studies were considered false-positives except for one. 11 Stress utilization in our cohort was of no yield and also was not associated with false-positives as it has been in other studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…recent studies have had variable results with positive stress test rates ranging from 3% to 6%. 11,12 However, all the positive stress tests in these studies were considered false-positives except for one. 11 Stress utilization in our cohort was of no yield and also was not associated with false-positives as it has been in other studies.…”
Section: Discussionmentioning
confidence: 98%
“…6-10 Subsequent studies have also suggested a low utility of routine stress testing in such observation patients, given the low true positive rate. 5,11,12 We hypothesized that observation and selective stress testing in patients age <40 with no history of coronary artery disease (caD), a nonischemic electrocardiogram (ecg), and a normal first troponin i were of very low utility [<1% acute coronary syndrome (acS) or Mace].…”
mentioning
confidence: 99%
“…2 Several recent studies suggest particularly little benefit, and potential harm, when routine cardiac testing is performed in low-risk eD populations under the age of 40 due to a high likelihood of false-positive or indeterminate test results. [8][9][10] Prasad et al, based on their interpretation of multiple nationalscale studies attempting to link diagnostic testing with cardiac outcomes, noted that although caD is increasingly diagnosed, the rates of aMi are failing to decline. [12][13][14][15][16] this may relate in part to the fact that a clearly defined, consensus strategy to risk stratify and guide the disposition of chest pain patients remains elusive, and the current practice of routine cardiac stress testing or advanced cardiac imaging may indeed have an unfavorable risk-benefit ratio for low-risk chest pain patients.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][17][18][19][20] instead, it highlights an area for further research aimed at clarifying and improving risk-stratification guidelines for chest pain patients in eDOUs and refining the way in which patients are selected to proceed to undergo provocative testing. [8][9][10]12 Our focus on patients with a positive provocative test and negative catheterization answered the initial question of whether or not an efficiency issue exists in the selection of patients who receive provocative testing in this setting. the next step -determining how to improve patient selection -will require further research into test results of all kinds: positive and negative, true and false.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation